TEOLOGI IMAN DAN PERBUATAN BERDASARKAN YAKOBUS 2: 17 DALAM KEHIDUPAN ORANG KRISTEN MASA KINI - Delsi Ayu; Moses Alfian Rallu; Tita Sanda Limbong (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study aims to analyze the theology of faith and works based on James 2:17 and to explain its relevance to the lives of contemporary Christians. A qualitative research method employing a literature review approach was used. Data were gathered through an examination of the Bible as well as various theological texts, biblical commentaries, scholarly journal articles, and other relevant academic sources. The analysis utilized a descriptive-analytical approach, incorporating exegesis and hermeneutics to understand the text's theological meaning and its implications for the lives of believers. The findings indicate that James 2:17 affirms that genuine faith is always manifested through works as the fruit of salvation, rather than as a prerequisite for obtaining it. Faith and works are complementary aspects of the Christian life. The implementation of this teaching is reflected in character formation, ministry, social concern, and the integrity of the believer's life. Consequently, the theology of James 2:17 remains relevant as a foundation for cultivating a Christian spirituality that is authentic and responsible, and capable of bearing witness to Christ within modern society.